Empowering Classroom English Proficiency through Communicative Peer Assessment - Rokhayani, Atik; Nurcahyo, Agung Dwi; Rukmini, Dwi; Fitriati, Sri Wuli (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Problems of delivering instructions have been faced by student teachers as the prospective EFL teacher candidates in many teaching practicum cases. This phenomenon has led to challenging discussions on how to cope with the problems. It also in one side brings about an awareness of the importance of empowering student teachers with good classroom English proficiency as one of the required skills that should be owned by English teacher candidates. This study reveals how Communicative Peer Assessment (CPA) works for developing the Classroom English proficiency of EFL teacher candidates. Referring to the research result CPA has been proven to give significant contribution to the teacher candidates in terms of some learning experiences, i.e. (a) allowing them to perform intensive communication practice; (b) stimulating the efforts of improving the classroom English performance through the peer teaching reflections; and (c) contextualizing the instructional English expressions.